2019
DOI: 10.3390/app9040747
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Behavior of Textile Reinforced Cementitious Composites Subjected to Fire

Abstract: The mechanical behavior of textile reinforced cementitious composites (TRC) has been a topic of wide investigation during the past 30 years. However, most of the investigation is focused on the behavior under ambient temperatures, while only a few studies about the behavior under high temperatures have been conducted thus far. This paper focused on the thermomechanical behavior of TRC after exposure to fire and the residual capacity was examined. The parameters that were considered were the fiber material, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The effect of an elevated temperature (120 • C and 200 • C) on the shear bond to masonry is treated in the feature paper by Askouni, Papanicolaou, and Kaffetzakis [7], using AR glass textiles with a normal weight and a lightweight mortar. The degradation of TRCs with SBR-coated carbon or AR glass textiles is treated in the paper by Kapsalis, El Kadi, Vervloet, De Munck, Wastiels, Triantafillou, and Tysmans [8].…”
Section: Trc In Structural and Materials Engineeringmentioning
confidence: 99%
“…The effect of an elevated temperature (120 • C and 200 • C) on the shear bond to masonry is treated in the feature paper by Askouni, Papanicolaou, and Kaffetzakis [7], using AR glass textiles with a normal weight and a lightweight mortar. The degradation of TRCs with SBR-coated carbon or AR glass textiles is treated in the paper by Kapsalis, El Kadi, Vervloet, De Munck, Wastiels, Triantafillou, and Tysmans [8].…”
Section: Trc In Structural and Materials Engineeringmentioning
confidence: 99%
“…Glass-fiber reinforced polymer (GFRP) components represent one of the most efficient solutions, due to their high tensile resistance, but the implementation of novel materials with enhanced benefits is also of interest [30][31][32][33][34], and attracted in the last few years the attention of several research investigations inclusive of experimental, analytical and finite element (FE) numerical studies. The thermo-mechanical structural behaviour of these assemblies under unfavourable conditions can be also relevant and should be properly taken into account [35,36]. Textile reinforced concrete can then be efficient also for improving the capacity of sandwich panels [37].…”
Section: Textiles and Fabrics With Traditional Buildings Materialsmentioning
confidence: 99%
“…In load-bearing structures, marginal TRC application issues arise from the ability to withstand high temperatures during fire. In previous work the main weakness of TRC was identified as the behavior of the homogenized carbon-fiber reinforcement with epoxy resin matrix at elevated temperatures [ 8 , 9 ]. Fire experiments showed that the load-bearing capacity of TRC at elevated temperatures depends on the interaction between the textile reinforcement and high-performance concrete (HPC).…”
Section: Introductionmentioning
confidence: 99%